Cuprous oxide microcrystals via hydrothermal approach: morphology evolution and photocatalytic properties. Issue 4 (12th February 2015) - Chai, Chunxia; Peng, Peng; Wang, Xinjun; Li, Ke
Abstract : Three morphological Cu2 O microcrystals with differently exposed planes were prepared. The exposed planes were clearly characterized by XRD and SEM, and the radial six hollow branches microcrystals with exposed {110} planes present a higher degradation efficiency to methyl orange (MO). Abstract : Cuprous oxide (Cu2 O) microcrystals with various morphologies were prepared under mild hydrothermal condition. The samples were characterized by means of XRD, SEM, and UV/DRS. The morphology of the as‐prepared Cu2 O microcrystals typically had cubic symmetry and the morphology evolution from radial, six hollow branches to truncated octahedra (again cubic) were realized by adding acetic acid. The peak relative intensity of XRD pattern shows that the exposed planes of samples is consistent with their morphology. A possible growth mechanism of Cu2 O microcrystals is also proposed. The behavior of adsorption and photocatalysis of Cu2 O microcrystals was investigated by degrading methyl orange (MO) in aqueous solution. The results show that the as‐prepared Cu2 O radial six hollow branches microcrystals with exposed {110} planes have higher degradation efficiency to methyl orange (MO) than cubic ones with exposed {100} planes and truncated octahedral with exposed {111} planes microcrystals.